Applied Cryptography and Network Security 9th International Conference, ACNS 2011, Nerja, Spain, June 7-10, 2011. Proceedings - Lopez, Javier; Tsudik, Gene.; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 9th International Conference on Applied Cryptography and Network Security, ACNS 2011, held in Nerja, Spain, in June 2011. The 31 revised full papers included in this volume were carefully reviewed and selected from 172 submissions. They are organized in topical sessions on malware and intrusion detection; attacks, applied crypto; signatures and friends; eclectic assortment; theory; encryption; broadcast encryption; and security services.
Electronic reproduction.
Keywords: Data encryption (Computer science) -- Congresses; Computer networks -- Security measures -- Congresses; Computer science; Computer Communication Networks; Data protection; Data encryption (Computer science).; Computer software; Computational complexity; Information Systems; Electronic books